HUBUNGAN PENGGUNAAN GATGED TERHADAP GANGGUAN EMOSI DAN PRILAKU REMAJA DI SMAN 1 SUMATERA BARAT - Amira Esti; Mona Yolanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
One form of technological development that is currently popular is gadgets. The benefits of technological developments have negative impacts such as gadget addiction. Gadget addiction has an impact on the development of children and adolescents. Children or teenagers who are addicted to gadgets will be preoccupied with themselves so that they ignore the environment around them and can ignore sleeping hours and reduce learning achievement. Based on an initial survey of 15 students at SMAN 1, students said they did not have close friends both at home and at school, had explosive emotions, and had no patience. This research is a quantitative research using a cross sectional research design. This study used a simple random sampling technique (Proportional Random Sampling), namely sampling which was carried out by giving equal opportunities to all individuals or population units randomly using the sampling method commonly used by researchers, with a total of 50 respondents. Univariate and Bivariate data processing using computerized Chi-Square analysis. Univariate results found (52%) teenagers using gadgets, (72%) teenagers having abnormal behavior and (56.3%) teenagers having abnormal emotions. There is a significant relationship between the use of gadgets and adolescent behavior. And there is a significant relationship between the use of gadgets and adolescent emotions. Keywords: Gadget, Emotional Disorder, Behavior, Teenagers